2020
DOI: 10.1029/2020gl089807
|View full text |Cite
|
Sign up to set email alerts
|

Phase Decoherence Within Intense Chorus Wave Packets Constrains the Efficiency of Nonlinear Resonant Electron Acceleration

Abstract: Electron resonant interaction with whistler mode waves is traditionally considered as one of the main drivers of radiation belt dynamics. The two main theoretical concepts available for its description are quasi-linear theory of electron scattering by low-amplitude waves and nonlinear theory of electron resonant trapping and phase bunching by intense waves. Both concepts successfully describe some aspects of wave-particle interactions but predict significantly different timescales of relativistic electron acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
159
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(172 citation statements)
references
References 70 publications
12
159
0
Order By: Relevance
“…Despite being inherently a nonlinear phenomenon, quasi-linear simulations are often successful in reproducing the observed effects of chorus wave-particle interactions [e.g., (21)], when individual waves are not large enough to induce nonlinear particle behavior such as phase trapping and nonlinear scattering (22,23). Other work has recently shown that, even for intense chorus waves, a quasi-linear approach can be a good approximation, as phase decoherence can mitigate nonlinear effects (24). Quasi-linear theory (25)(26)(27) describes local acceleration as diffusion in momentum space, from low energy to high energy.…”
Section: Effect Of Changing Density On the Diffusion Coefficientsmentioning
confidence: 99%
“…Despite being inherently a nonlinear phenomenon, quasi-linear simulations are often successful in reproducing the observed effects of chorus wave-particle interactions [e.g., (21)], when individual waves are not large enough to induce nonlinear particle behavior such as phase trapping and nonlinear scattering (22,23). Other work has recently shown that, even for intense chorus waves, a quasi-linear approach can be a good approximation, as phase decoherence can mitigate nonlinear effects (24). Quasi-linear theory (25)(26)(27) describes local acceleration as diffusion in momentum space, from low energy to high energy.…”
Section: Effect Of Changing Density On the Diffusion Coefficientsmentioning
confidence: 99%
“…Such short wave packets and their huge sweep rates apparently cannot be explained by nonlinear trapping in a single wave. Instead, they could simply result from a superposition of two waves, leading to wave amplitude modulation at the frequency difference Δ ω (Tao et al., 2013; Zhang, Mourenas, et al., 2020).…”
Section: A Scheme Of Realistic Chorus Wave Packet Generationmentioning
confidence: 99%
“…2018; Zhang et al. 2020 a ). Such a chaotization of wave fields is likely partly driven by currents of resonant electrons (Nunn et al.…”
Section: Discussionmentioning
confidence: 99%
“…2020 a ; Zhang et al. 2020 a ). Thus, an important further development of the mapping technique for nonlinear wave–particle interaction would require modifications of the phase trapping model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation